Treatment of severe nosocomial pneumonia: a prospective randomised comparison of intravenous ciprofloxacin with imipenem/cilastatin. Issue 12 (1st December 2000) - Torres, A; Bauer, T T; León-Gil, C; Castillo, F; Alvarez-Lerma, F; Martínez-Pellús, A; Leal-Noval, S R; Nadal, P; Palomar, M; Blanquer, J; Ros, F
Abstract : BACKGROUND: A prospective multicentre study was undertaken to compare the efficacy of intravenous ciprofloxacin or imipenem in the treatment of severe nosocomial pneumonia requiring mechanical ventilation. METHODS: Patients with a clinical suspicion of pneumonia were randomised to receive either ciprofloxacin (800–1200 mg/day) or imipenem (2–4 g/day) in doses adjusted for renal function and specimens of the lower respiratory tract were taken. Patients were included in the study when specimens showed significant growth for potentially pathogenic microorganisms in quantitative bacterial cultures (n = 75, ciprofloxacin 41/75 (55%); imipenem 34/75 (45%)). The clinical and bacteriological success rates were the primary and secondary efficacy variables. An intent-to-treat analysis was performed for all randomised patients who received at least one dose of the study medication (n = 149, ciprofloxacin 72/149 (48%), imipenem 77/149 (52%)). RESULTS: The success rates were generally good, but neither the clinical success rates (ciprofloxacin, 29/41 (71%), imipenem, 27/34 (79%); 95% CI –10.8 to 28.1; p = 0.435) nor the bacteriological response rate (ciprofloxacin, 20/41 (49%), imipenem, 17/34 (50%); 95% CI –21.5 to 23.9; p = 1.0) were significantly different between the study arms. Pseudomonas aeruginosa was recovered in 26/75 patients (35%) and clinical (ciprofloxacin, 10/14 (71%), imipenem, 8/12 (67%); 95% CI –40.4 to 30.9; p = 1.0) and bacteriological response rates (ciprofloxacin, 7/14 (50%), imipenem, 3/12 (25%), 95% CI –60.9 to 10.9, p = 0.247) were not significantly different in this subgroup of patients. Resistance of Pseudomonas aeruginosa developed in 5/26 cases (19%), 1/14 (7%) to ciprofloxacin and 4/12 (33%) to imipenem (p = 0.147), and the mortality was 12/75 (16%) with no difference between treatment groups (ciprofloxacin, 8/41(24%), imipenem 4/34 (17%); p = 0.362). The clinical response was evaluable in 109/149 patients (73%) in the intent-to-treat analysis and was successful in 74/109 patients (68%). The clinical response rates were also not significantly different in the intent-to-treat analysis (ciprofloxacin, 34/52 (65%), imipenem, 40/57 (70%); 95% CI –12.8 to 22.3; p = 0.746). CONCLUSIONS: Treatment with either ciprofloxacin or imipenem was effective in a selected group of patients with microbiologically confirmed, severe nosocomial pneumonia requiring mechanical ventilation. Although no differences between the study medication could be documented in this trial, smaller differences between treatment arms may have been missed because of sample size limitations.